Periodization of Plyometrics: Is There an Optimal Overload Principle?. Issue 10 (October 2021) - Lievens, Maarten; Bourgois, Jan G.; Boone, Jan
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Lievens, M, Bourgois, JG, and Boone, J. Periodization of plyometrics: Is there an optimal overload principle? J Strength Cond Res 35(10): 2669–2676, 2021—This study investigated the acute and chronic effects of 3 plyometric training (PT) programs with equal training loads (intensity × volume × frequency) on speed, agility, and jumping performance. Forty-four male recreational team sport athletes were either assigned to a program that increased training volume with exercises of mixed intensity (Mix), kept training volume equal and increased exercise intensity (LowHi), increased training volume and kept exercise intensity low (Low), or to a control group (Control). Subjects were trained twice a week for 8 weeks and were tested for 5- (5 m) and 10-m sprint (10 m), 5 × 10-m shuttle run (5 × 10 m), squat jump (SJ), countermovement jump without and with arm swing, and standing broad jump. Five-, 10- and 5 × 10-m performance did not change ( p > 0.05) after the PT program. Jumping performance, except for SJ ( p = 0.114), improved significantly ( p < 0.05) in the PT groups compared with the control group. However, no mutual differences ( p < 0.05) were established between plyometric groups. In addition, it was shown that a PT of high intensity was more likely to affect performance and blood inflammation markers in the following days. To conclude, PT programs following a different overload pattern, i.e., different combination of volume and intensity, but equal training load showed similar performance effects in recreationally trained men. However, before competition, a PT of low intensity is preferred over a PT of high intensity to avoid a decline in performance.